2017
DOI: 10.1155/2017/7236956
|View full text |Cite
|
Sign up to set email alerts
|

Field Tests to Investigate the Penetration Rate of Piles Driven by Vibratory Installation

Abstract: Factors directly affecting the penetration rate of piles installed by vibratory driving technique are summarized and classified into seven aspects which are driving force, resistance, vibratory amplitude, energy consumption, speeding up at the beginning, pile plumbness keeping, and slowing down at the end, from the mechanism and engineering practice of the vibratory pile driving. In order to find out how these factors affect the penetration rate of the pile in three major actors of vibratory pile driving: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the field, achieving accurate control of the horizontal motion of sheet piles during both driving and extraction can be challenging. Grizi et al [20] reported that the amplitude of the horizontal motion components of sheet piles is typically less than 30% of the vertical motion component. Therefore, the horizontal motions in this article are not considered.…”
Section: Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field, achieving accurate control of the horizontal motion of sheet piles during both driving and extraction can be challenging. Grizi et al [20] reported that the amplitude of the horizontal motion components of sheet piles is typically less than 30% of the vertical motion component. Therefore, the horizontal motions in this article are not considered.…”
Section: Test Resultsmentioning
confidence: 99%
“…Lee et al [19] conducted vibration-driven field tests on full-scale U-shaped piles to investigate the dynamic characteristics of the piles with and without clutch friction. Qin et al [20] conducted field experiments on vibration-driven sheet piles in various soil conditions and investigated the effect of driving force, resistance, amplitude, and energy consumption on pile penetration rates. Grizi et al [21] presented ground motion measurements during the driving of full-scale H-shaped piles using a diesel hammer, revealing the propagation and attenuation of the wave source.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists analysing the influence of the impact energy on the vibrations of the ground and objects use properties in the amplitude's form of the propagating wave, its frequency, or the speed of movement of soil particles. The Bornitz equation, describing the damping of vibrations at selected points of the ground, is commonly used [21][22][23][24][25][26]:…”
Section: Introductionmentioning
confidence: 99%
“…Its precise determination would be possible only with homogeneous soil. This situation practically does not occur, because the soil is combined with many layers, such as sand, silt, clay, and rock [26,27]. The components of the layers may have different granulation, the thickness of the layers may be varied, and there may be layers combining various components.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that by applying more frequency and low energy, more penetration is achieved. In a recent study done by Qin et al (2017), numerous field tests were compiled to assess the effect of seven influencing parameters in the vibratory driving system on penetration rate of three different sheet pile sections. Results suggest that the effect of vibratory driving becomes significant at later stages of the penetration.…”
Section: Introductionmentioning
confidence: 99%